5 voices : how to communicate effectively with everyone you lead - Kubicek, Jeremie; Cockram, Steve (Hoboken : Wiley, 2016)
"Discover your leadership voice and unlock your potential to influence others 5 Voices is the code for unlocking your capacity to have honest conversations and build deeper, more authentic relationships with your teams, your families and your friends. In order to lead others effectively, we need a true understanding of ourselves, our natural tendencies and patterns of behavior. In learning what your leadership voice sounds like to others, you will discover what it feels like to be on the other side of your personality, as well as how to hear and value others' voices, namely the Pioneer, the Connector, the Creative, the Guardian, and the Nurturer. Once you understand your own leadership voice, you'll discover how best to communicate with each of the other voices, which will transform your communication at every level of relationship, both personal and professional. In mastering the 5 Voices of leadership, you will increase your emotional intelligence, allowing you to gain a competitive advantage as a leader. You will also be equipped with a simple, easy to remember vocabulary that, when shared, has a track record for decreasing the drama, misunderstanding and miscommunication in all spheres of influence. Are you focused on relationships, values, and people? Or are you oriented more toward tradition, money, and resources? Do you know how others hear your voice? Do you appreciate the contributions of others on your team? This book will help you identify your natural leadership style, and give you a framework for leveraging your strengths. Find your foundational leadership voice Learn to hear and value the voices of others Know yourself before leading others Connect and communicate well with team, family and friends All five leadership voices come with their own particular set of strengths, and all have areas for growth. Understanding both sides of the equation is the key to taking your leadership to the next level and is the secret to increasing your ability to influence your team, family and friends. 5 Voices is a simple key which unlocks complicated relational dynamics and improves the health and alignment of all your relationships"--
Machine generated contents note: Introduction Why We Need the 5 Voices Vocabulary Section 1: The Voices of a Team Chapter 1: The Voice Called Yours Hearing Your Voice for the First Time The Other Side of Your Voice Understanding the Code Chapter 2: How the 5 Voices Work Understanding the 5 Voices Personality Quotient Nature, Nurture, Choice Know Yourself, Lead Yourself How the 5 Voices Were Created Chapter 3: Discovering Your Voice 5 Voices Definitions Assumptions 5 Voices Assessment Voice Order Chapter 4: The Nurturer Voice What They Are Really Thinking? At Their Best Questions they're really asking Negative Impact Insights for Nurturers Chapter 5: The Creative Voice Unspoken Assumptions Bringing Their Best What They Are Really Asking Negative Impact How to Help the Creative Chapter 6: The Guardian Voice What They Are Really Thinking At Their Best Questions They Are Really Asking Negative Impact Chapter 7: The Connector Voice What They Are Really Thinking At Their Best Questions They Are Really Asking Negative Impact Chapter 8: The Pioneer Voice What They Are Really Thinking At Their Best Questions They Are Really Asking Negative Impact Discovering the Pioneer Voice Section 2: How to Interact With Each Voice Chapter 9: Understanding Your Weapons System The Pioneer Weapons System The Nurturer Weapons System The Creative Weapons System: The Creative Feeler The Creative Weapons System: The Creative Thinker The Guardian Weapons System The Connector Weapons System Chapter 10: Knowing Your Rules of Engagement NURTURER CREATIVE GUARDIAN CONNECTOR PIONEER Chapter 11: Voice Control - Mastering Your Voice Understanding Your Voice Order Being the Champion What Each Voice Champions 70/30 Principle Cultural Bias Mastering Your Voices for the Benefit of All Section 3: Building Powerful and Effective Teams Chapter 12: Leading Effective Change Communicating Effective Change Creating an Advisory Group Building the Bridge Chapter 13: 100X Team Challenge What Does Your Team Really Look Like? Confronting the Cold Honest Truth Principles or Personalities? The 100X TEAM The GiANT Team Chapter 14: Change Your World Transformational Leadership Resources About GiANT Worldwide Speaking Acknowledgements.
Includes index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Leadership; Self-actualization (Psychology); Electronic books